Efektivitas dan Efisiensi Penyelesaian Sengketa Kekayaan Intelektual melalui Arbitrase dan Mediasi berdasarkan Undang-Undang Nomor 30 Tahun 1999 - Sudjana Sudjana (Ajudikasi : Jurnal Ilmu Hukum, 2018)
This review discusses the effectiveness and efficiency of dispute resolution of intellectual property through Arbitration compared to Mediation under Law Number 30 of 1999.Approach method used is normative juridical, that is studying national legislation. Specific descriptive analytical research in the sense of describing the issues discussed and analyzed. The research stage is done through literature study to examine the primary law material such as Law Number 30 of  1999 Concerning Arbitration and Alternative Dispute  Resolution. Furthermore, secondary law material is done through expert opinion, and tertiary legal material is digital source (internet). Data collection techniques are conducted through document studies, which are conducted by reviewing documents on intellectual property dispute resolution. Then the method of data analysis is done through normative qualitative, it means to study the problem do not use statistic formula, but starting from the principles of law.The results of the study show that the settlement of intellectual property disputes through Arbitration and  Mediation each has advantages and disadvantages. Mediation is more effective and efficient than Arbitration relating to stakeholder relations, atmosphere, results achieved, and costs. However, in terms of legal certainty, arbitration is more effective because the decision is final and binding. Keywords: Dispute Resolution, Intellectual Property, Arbitration, Mediation.